Generation Y: An Agenda for Future Visitor Attraction Research. (17th April 2013) - Leask, Anna; Fyall, Alan; Barron, Paul
ABSTRACT This study provides a comprehensive secondary‐based synthesis of previous studies on the profile and patterns of consumption of Generation Y, their consumption experiences and the role of information communication technologies and social media in determining their emerging patterns of behaviour at visitor attractions. The paper concludes by advancing a management‐oriented attraction research framework specific to Generation Y with a set of research propositions proposed to stimulate further research and management action on this specific and highly influential generational cohort. Copyright © 2013 John Wiley & Sons, Ltd.